2014
DOI: 10.11591/edulearn.v8i2.219
|View full text |Cite
|
Sign up to set email alerts
|

Readiness of Makassar Public High School Counsellors in Coping Organizational Change

Abstract: This study aims to determine the readiness of State High School counsellors in the city of Makassar who are confronted with organizational change. The assessment is viewed from the aspect of preparedness of counsellors that includes self-esteem, optimism and perceived control. A mixed method was used in this study that was simultaneously embedded. Survey questionnaires were distributed to 68 counsellors of State High Schools in Makassar for purposes of quantitative analysis, while an interview was conducted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 17 publications
(6 reference statements)
2
1
0
Order By: Relevance
“…This result is also in accordance with what Donatta (2018) revealed optimism is a condition of individuals who find beliefs that have benefits over something that will happen in the future. The results of this study are also supported by previous research from Dasmawati and Boon (2014) which mentioned a positive relationship between optimism and readiness for change. Research from Nwanzu and Babalola (2019) found that there is a relationship between optimism and readiness for change.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…This result is also in accordance with what Donatta (2018) revealed optimism is a condition of individuals who find beliefs that have benefits over something that will happen in the future. The results of this study are also supported by previous research from Dasmawati and Boon (2014) which mentioned a positive relationship between optimism and readiness for change. Research from Nwanzu and Babalola (2019) found that there is a relationship between optimism and readiness for change.…”
Section: Resultssupporting
confidence: 89%
“…The results of the study show that optimism positively affects the readiness to change in bank employees. This research was also supported by Dasmawati and Boon (2014) the results of the study found that optimism affects the readiness to change in health counselors in Makassar. Research related to the effect of agility on readiness to change has been studied by Vaishnavi, et al (2019), the results of the study found that agility affects readiness to change.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation